Draft BS EN IEC 61753-071-02/AMD1. Fibre optic interconnecting devices and passive components. Performance standard. Part 071-02: Non-connectorized single-mode fibre optic 1 × 2 and 2 × 2 spatial switches for category C. Controlled environments (25th August 2023) - British Standards Institution,
No abstract available